2007
DOI: 10.1111/j.1525-139x.2007.00384.x
|View full text |Cite
|
Sign up to set email alerts
|

Review: Cognitive Function in Chronic Kidney Disease

Abstract: Chronic kidney disease (CKD) is a growing public health problem. The incidence of kidney failure is rising in all age groups but particularly in older adults. Individuals in all stages of CKD are at higher risk for development of cognitive impairment and this may be a major determinant in their quality of life. Furthermore, cognitive impairment is associated with an increased risk of death in dialysis patients. Cerebrovascular disease is a strong risk factor for development of cognitive impairment and vascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
166
0
21

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(191 citation statements)
references
References 95 publications
(106 reference statements)
3
166
0
21
Order By: Relevance
“…Large randomised clinical trials have consistently demonstrated that using higher haemoglobin targets has resulted in worse outcomes including death. 10,13 Finally, the process of dialysis causes significant haemodynamic shifts, these changes in blood flow are hypothesized to adversely affect endorgans and result in perfusion related brain injury. 12 As such, strategies that improve haemodynamic stability such as cooling the dialysate, haemodiafiltration or lower ultrafiltration rate may be beneficial.…”
Section: Strokementioning
confidence: 99%
“…Large randomised clinical trials have consistently demonstrated that using higher haemoglobin targets has resulted in worse outcomes including death. 10,13 Finally, the process of dialysis causes significant haemodynamic shifts, these changes in blood flow are hypothesized to adversely affect endorgans and result in perfusion related brain injury. 12 As such, strategies that improve haemodynamic stability such as cooling the dialysate, haemodiafiltration or lower ultrafiltration rate may be beneficial.…”
Section: Strokementioning
confidence: 99%
“…60 Nontraditional vascular risk factors, such as hyperhomocysteinemia, hypercoagulable states, inflammation, and oxidative stress, have also been linked to cognitive impairment. 61 These factors could accelerate the progression of atherosclerosis and vascular endothelial dysfunction, both of which are associated with dementia risk. 62,63 Interestingly, elevated homocysteine levels are present in 85% of dialysis patients but only 10% of the general population.…”
Section: Potential Causes Of Cognitive Impairment In Patients With Ckdmentioning
confidence: 99%
“…Interestingly, patients with early stages of CKD already show cognitive impairment [20]. Depending on CKD stage, CKD is frequently associated with prevalence of cognitive impairment in different domains including executive function, information processing speed, memory and language, which range from 17% to 87% [7,[9][10][11][12][13][14][15].…”
Section: Prevalence Of Chronic Kidney Diseasementioning
confidence: 99%
“…The MiniMental State Examination (MMSE) test is currently the most widely used screening tool for cognitive impairment in the general population, however it is not able to detect mild cognitive impairment and especially not impairment in executive function which is highly prevalent in CKD [40]. For the CKD context, further the Cognitive Capacity Screening Examination (CCSE) has been suggested to complement MMSE to evaluate cognitive function and the Kidney Disease Quality of Life (KDQOL) self-report instrument including a cognitive function subscale (KDQOL-CF) to additionally assess health-related quality of life [12]. To complement cognitive screening, magnetic resonance imaging could be useful to detect cerebrovascular disease as important determinant of cognitive impairment in CKD.…”
Section: Clinical Implications Of Cognitive Impairment In Chronic Kidmentioning
confidence: 99%
See 1 more Smart Citation